2015
DOI: 10.1111/jsap.12305
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of suspected idiopathic bilateral C2 hypertrophic ganglioneuritis in dogs

Abstract: Bilaterally symmetric C2 neuritis likely represents idiopathic hypertrophic ganglioneuritis. Staffordshire bull terriers appear over represented. Immunosuppressive doses of corticosteroids should be considered for clinically significant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Enlargement of the peripheral nerves is a feature of various peripheral neuropathies, for which the term “hypertrophic neuritis” usually indicates the unique pathological changes associated with onion bulb formation [ 10 ]. Hypertrophic neuritis is a non-neoplastic condition, mainly causing demyelinating neuropathy in humans and dogs [ 7 , 10 , 12 , 13 ]. Many cases in humans are characterized by chronic inflammatory demyelinating polyneuropathy (CIDP) accompanied by the formation of onion bulbs composed of proliferated Schwann cells and chronic focal inflammation [ 1 , 10 , 13 ].…”
mentioning
confidence: 99%
“…Enlargement of the peripheral nerves is a feature of various peripheral neuropathies, for which the term “hypertrophic neuritis” usually indicates the unique pathological changes associated with onion bulb formation [ 10 ]. Hypertrophic neuritis is a non-neoplastic condition, mainly causing demyelinating neuropathy in humans and dogs [ 7 , 10 , 12 , 13 ]. Many cases in humans are characterized by chronic inflammatory demyelinating polyneuropathy (CIDP) accompanied by the formation of onion bulbs composed of proliferated Schwann cells and chronic focal inflammation [ 1 , 10 , 13 ].…”
mentioning
confidence: 99%
“…One case report described a full recovery following surgical removal of an enlarged C2 spinal nerve, which was later confirmed to be focal hypertrophic ganglioneuritis 29 . Similarly, a good prognosis was reported in a retrospective study in 12 dogs with bilateral C2 hypertrophic neuritis 28 . All clinically affected dogs in the study improved with either immunosuppressive doses of steroid.…”
Section: Discussionmentioning
confidence: 54%
“…However, due to the rapid recovery in the absence of specific medical management, infectious neuritis was felt very unlikely. Hypertrophic neuritis is a rare inflammatory disease of unknown origin which often affects the cervical region unilaterally or bilaterally and can be focal or multifocal 28 . Due to similar findings on clinical examination and advanced imaging modalities, it has been suggested that hypertrophic neuritis can mimic spinal nerve neoplasia leading to misdiagnosis where the underlying cause might in fact be inflammatory in origin.…”
Section: Discussionmentioning
confidence: 99%
“…Our study has several limitations: the first limitation concerns the accuracy of data collection in a study that encompasses a period of almost 4 years and that in many cases did not have further investigations able to rule out concomitant conditions and/or a histopathological confirmation of the diagnosis. However, specific diagnostic guidelines were followed for each disease (Kraft et al , Lowrie et al , Granger et al , Carrera et al , Joslyn et al , De Decker et al ). A second important limitation is the inclusion of cases only referred to the Neurology and Neurosurgery Service of a single referral practice, which might have under‐ or overestimated specific diseases.…”
Section: Discussionmentioning
confidence: 99%